2010
DOI: 10.1051/radiopro/2009030
|View full text |Cite
|
Sign up to set email alerts
|

Determination of uranium at ultra trace level in packaged drinking water by laser fluorimeter and consequent ingestion dose

Abstract: Precise and accurate estimation of natural radioactivity is essential in order toappraise the radiation dose to the member of public due to various intakes. In the present study, an attempt has been made to estimate the uranium content in packaged drinking water by laser induced fluorimetry and then to calculate the committed effective dose. Sixty packaged drinking water samples of different brands were analysed for uranium content. The total uranium content in these samples was found to be in the range of 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The concentrations of uranium measured in the present work shows that they are well within the suggested limit. A recent study conducted in the packaged drinking water samples in India found that the range of uranium in water between 0.04µg/l to 3.88 µg/l (Sahoo et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of uranium measured in the present work shows that they are well within the suggested limit. A recent study conducted in the packaged drinking water samples in India found that the range of uranium in water between 0.04µg/l to 3.88 µg/l (Sahoo et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…For the modified laser fluorimetric method validation, eight water samples were analyzed for uranium isotopes by alpha spectrometry. The combined 234 U and 238 U activities were converted to mass (μg/L), using the natural isotopic abundances and the specific activity of both uranium isotopes [22], and were compared with their corresponding values measured by laser fluorimetry, as shown in figure 2.…”
Section: Methods Validationmentioning
confidence: 99%
“…In order to convert the mass of total uranium (μg L −1 ) to activity (Bq L −1 ), two approaches were followed. The first approach was to fractionate the determined uranium mass for each water sample into three isotopic activities ( 238 U, 234 U, 235 U) according to their mass abundances (99.27, 0.0055, and 0.72% respectively) and their specific activities (12.4, 230.14×10 3 , and 79.2 Bq mg −1 respectively) [22]. The second approach was to assume that the total specific activity of the natural uranium is 25.4 Bq mg −1 and to multiply this value by the determined uranium concentrations and the DCF of 4.5×10 −8 [22,26].…”
Section: Dose Assessmentmentioning
confidence: 99%
“…Fluorescence measurements provide information about the uranium content in the sample. (Sahoo et al, 2009(Sahoo et al, , 2010. The standard addition technique is used to evaluate each sample due to changes in the chemical composition of the collected water samples and to avoid the matrix effect.…”
Section: Analysis Of Physicochemical Parametersmentioning
confidence: 99%